Desarrollo cognitivo y emocional en estudiantes de tercer ciclo de las instituciones educativas de nivel primaria Caballococha, Ramón Castilla 2024 - Reyna Campos, Maykol Luis (2025)
The study aimed to establish the relationship between cognitive and emotional development in third-cycle students from educational institutions in Caballococha Ramón Castilla in 2024. A non-experimental, cross-sectional, field-based, bivariate, and relational design methodology was employed. The total population consisted of 668 students, of which a sample of 228 was selected. Surveys and cognitive development tests were administered for data collection. The analysis indicated a significant association between the dimensions of Cognitive and Emotional Development. The results revealed that all children with deficient cognitive development exhibited a regular emotional level, while those with regular cognitive development showed a higher representation in the notable emotional category. The normality test, conducted using the Kolmogorov-Smirnov statistics, indicated that the variables did not follow a normal distribution, necessitating the use of the non parametric Spearman's rho test for hypothesis testing. With a p-value of .000 and a rho coefficient of .398, it was concluded that adequate cognitive development is associated with favorable emotional development, underscoring the necessity to integrate both dimensions within the educational context.